The Relationship of Fiber Supplements and Cholesterol Levels in Hypercholesterolemia Patients at The Pati II Health Center in 2025 - Risa Wulandari; Dewi Hartinah; Diana Tri Lestari (CV. Inara, 2026)
The phenomenon of hypercholesterolemia has become problematic both in the world and in Indonesia because high cholesterol levels (hypercholesterolemia) are the main risk factor for non-communicable diseases (NCDs) and have implications for an increase in mortality due to hypercholesterolemia, which is 73%. Hypercholesterolemia is closely related to risk factors such as age, gender, diet, smoking, lack of physical activity, BMI, and other related clinical conditions such as triglycerides, obesity, diabetes mellitus, and hypertension. The purpose of the study was to determine the relationship between fiber supplements and cholesterol levels in hypercholesterolemia patients at the Pati II Health Center in 2025. This research method is a correlation analytical research with a cross sectional approach. A sample was taken from a part of the research population with a sample of 56 respondents with a sampling formula using the slovin formula and the sampling criteria used was purposive sampling. The measuring tools used are observation sheets and GCU Easy Touch tools. The data analysis used univariate and bivariate analysis with a spearman rank correlation test with a significant value of a=0.05. The results showed that as many as 29 (51.8%) respondents consumed fiber supplements. High cholesterol levels were 22 (39.3%) of respondents. The results of the study concluded that there was a relationship between fiber supplements and cholesterol levels in patients at the Pati II Health Center in 2025 with a p value of 0.001.